(untitled) (The Research of Medical Science Review, 2024)
Background: The aim of this survey is to evaluate the diagnostic accuracy of gray scale ultrasound in determining the urolithiasis in those patients having renal colic, in terms of sensitivity and specificity while taking Non-contrast computed tomography as the gold standard. Objective: This study's goal is to assess the diagnostic precision of ultrasound in ureteric calculus using Computed tomography scan Phylogram as the gold standard, which allowed for more effective therapy. Materials and Method: This cross-sectional study was carried out in tertiary care teaching hospitals in KPK Pakistan. A criteria was built to involved the 290 participants. The teaching hospital comprised was the Hayatabad Medical Complex Peshawar. Questionnaire was arranged the usefulness of which is examined by carrying out a pilot study by choosing radiologic staffs from the mentioned hospitals. Data was taken together by filling the questionnaire and analyzed using SPSS software. Results: A total of 240 participants were registered in this survey. The mean age was 43 years. In the current investigation, it was determined that ultrasonography had the following characteristics for the identification of ureteric calculi: sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy, which were found to be correspondingly 55%, 75%, 88%, 51.2%, and 79.3%. While the sensitivity and specificity of computed tomography were 100% and 100%, respectively. Conclusion: ultrasound has nearly identical patient outcomes to computed tomography. The decision is based on the accessibility of each technology and the radiologist's experience. The computed tomography will identify more lithiasis, but combining X-ray KUB and ultrasound will, with some effort, yield findings that are practically equivalent while exposing the patient to less or none of X-ray radiation. Only those patients who have had a negative ultrasound and plain X-ray and have clinical symptoms of a severe colic ought to get a NCCT